Development of an IoT-Based System for River Siren Control and Height Detection Utilizing LoRa and Solar Cell Technology - Mardiana; Yuvina; Nst, Tuti Adi Tama; Benu, Siti Maretia (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
We need a tool that can measure river water levels automatically based on IoT so that water level data can be received in real time. This tool uses an Arduino microcontroller which functions to convert analog data into digital by measuring water level using an ultrasonic sensor so that the data can be converted into digital water level data and displayed via the internet and a buzzer or siren as a danger warning when the water level rises high as well as water level data. can be monitored as a whole. Apart from that, this tool is equipped with LoRa communication. This LoRa can send signals as far as 15 km without obstructions, so even if there is no internet, this tool can still work and can be used in areas without electricity because it uses solar cells as a power supply. If the water reaches the maximum limit, the siren will sound and stop again when the water in the river is at normal level.